Alloy characterization semiconductors by Raman spectroscopy - Espinoza Carrasco, Veronica (2009)
The effect of the structural disorder in the Raman scattering of the coupled plasmon - LO phonon modes was studied in doped AlxGa1-xAs/Si alloys. The asymmetry in the Raman lines allows us the observation of these modes because the translational symmetry of the crystal was destroyed. The analysis of the position and shape of their spectral lines provides information on the concentration of carriers and the effects of structural disorder of the material. We note that the effective concentration of carriers in Raman measure differs from the nominal values given by the manufacturer, which suggests possible losses in the evaporation process of the silicon or the excess of evaporation time. The results were verified by measurement of Capacitance versus Voltage for two samples.